Perceptions of teachers regarding the significance and level of implementation of sexual education content for ethnic minority students in Vietnam - Nguyen, Sau Thi Ut; Nguyen, Son Trong (Journal of Education and e-Learning Research, 2023)
Comprehensive sex education is one of the most critical tools for providing young people with the knowledge they require to make wise decisions. Sex education has a reputation for being delicate due to the intimate and personal nature of the topic. A survey involved 45 administrators (including principals, vice principals and heads of expertise), 15 teachers of social science disciplines and 15 classroom teachers. The results indicated that the importance of sex education for ethnic minority students was not appreciated by teachers and that the implementation level of sex education content and its form were low and ineffective. The study highlights topics that educators must consider when establishing strategic plans for successful and acceptable sex education in a societal context or with ethnic minority students.